EFFECT OF WORKING CAPITAL, COMPANY SIZE, AND COMPANY GROWTH ON PROFITABILITY AND COMPANY VALUE - Hama, Aloisius; Santosa, Herlambang Pudjo (PEOPLE: International Journal of Social Sciences, 2018)
This study aimed to analyze whether working capital, company size, and company growth affected the profitability of companies listed on Indonesian Stock Exchange from 2012 to 2016. Therefore, explanatory research was applied to understands the impacts of those varaibles. In this study, samples were taken with saturated sampling technique with secondary data during data collection and documentation period in the 129 manufacturing companies listed on Indonesian Stock Exchange from 2012 to 2016. Then, the data were analyzed and presented with the Partial Least Square. As the results, the data indicated significant consequence of working capital towards profitability. The company size also significantly affected the company value. In contrast, the company growth had no significant effect on the company value, but had significant impact on profitability of the company value.